2011
DOI: 10.3758/s13414-011-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-transient luminance changes do not capture attention

Abstract: The processing of luminance change is a ubiquitous feature of the human visual system and provides the basis for the rapid orienting of attention to potentially important events (e.g., motion onset, object onset). However, despite its importance for attentional capture, it is not known whether a luminance change attracts attention solely because of its status as a sensory transient or can attract attention at a relatively high cognitive level. In a series of six experiments, we presented visual displays in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Are these dimensions less important in holding viewers’ moment-to-moment attention. We know that luminance changes can grab attention (Cole, Kuhn, & Skarratt, 2011 ; Spehar & Owens, 2013 ; Theeuwes, 1991 ), but film luminance is a more a property of a scene than it is of the shots that make it up. That is, luminance is less likely to change across shots within a scene than across shots at a scene boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Are these dimensions less important in holding viewers’ moment-to-moment attention. We know that luminance changes can grab attention (Cole, Kuhn, & Skarratt, 2011 ; Spehar & Owens, 2013 ; Theeuwes, 1991 ), but film luminance is a more a property of a scene than it is of the shots that make it up. That is, luminance is less likely to change across shots within a scene than across shots at a scene boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this contrasts markedly with what was previously assumed about IOR from classical precueing studies in which participants perform alone. For instance, Cole et al (2011a) showed that even when observers are aware that an occluded visual event has taken place in a spatial location, they do not inhibit it. The experiment involved participants having to detect a target appearing in a cued or uncued location.…”
Section: Social Ior and New Insights Into Human Cognitionmentioning
confidence: 99%
“…As the shape contracted, the new object appeared behind and was then revealed in a location previously seen to be unoccupied. As with Cole et al (2011a), participants were aware that a scene change had taken place, but had not seen the accompanying transient that signaled its arrival. Results showed that new objects failed to capture attention under these conditions, yet they did attract attention when the annulus was seen to move behind the search items thus rendering a visible onset (but see Cole et al, 2011a, Experiment 6).…”
Section: Social Ior and New Insights Into Human Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light adaptation is widely understood as the combination of a series of mechanisms that occur in the retina (Barrionuevo et al, 2018;Gloriani et al, 2016), and even the processing of luminance changes is a low-level sensory condition (Cole, Kuhn, & Skarratt, 2011). When adaptation luminance changes from photopic to mesopic values, the visual spectral sensitivity curve gradually shifts as a consequence of the transition from a cone response to a rod-cone response (i.e., the Purkinje effect).…”
mentioning
confidence: 99%